(untitled) (Journal of Mechanical Engineering, 2015)
Numerical simulation of the thunderstorm event occurred over Srimangal, Bangladesh at 1200 UTCon 21 May 2011 have been carried out using Advance Research dynamic core of Weather Research andForecasting Model (WRF-ARW). The WRF model was run in a domain at 9 km horizontal resolution using sixhourly NCEP-FNL datasets from 0000UTC of 21 May to 0000UTC of 22 May 2011 as initial and boundaryconditions. Hourly outputs have been analyzed to asses and/or compare the model performance. The WRFmodel captured the studied thunderstorm event on 21 May 2011 in reasonably well with some spatial andtemporal biases in the results. But the model simulated 24-h rainfall over the country as a whole overestimatedthe rainfall by 46.72% compared to that of Bangladesh Meteorological Department (BMD) observation.